Rank-based biomarker index to assess cadmium ecotoxicity on the earthworm Eisenia andrei - Panzarino, O; Hyršl, P; Dobeš, P; Vojtek, L; Vernile, P; Bari, G; Terzano, R; Spagnuolo, M; de Lillo, E (Chemosphere, 2016)
A proper soil risk assessment needs to estimate the processes that affect the fate and the behaviour of a contaminant, which are influenced by soil biotic and abiotic components. For this reason, the measurement of biomarkers in soil bioindicator organisms, such as earthworms, has recently received increasing attention. In this study, the earthworm Eisenia andrei was used to assess the pollutant-induced stress syndrome after exposure to sublethal concentrations of Cd (10 or 100 μg g(-1)) in OECD soil, after 14 d of exposure. Cadmium bioaccumulation and potential biomarkers such as catalase (CAT), hydrogen peroxide (H2O2), glutathione-S-transferase (GST), malondialdehyde (MDA), phenoloxidase (PO), metallothioneins (MTs) and genotoxic damage were determined. Results suggested that the exposure to 10 and 100 μg g(-1) Cd significantly increased Cd bioaccumulation, MTs and MDA; 100 μg g(-1) Cd contamination evidenced significantly higher values of H2O2 content and PO activity; CAT activity was inhibited at the higher concentration while GST and Comet assay did not show any significant differences from the control. Rank-based biomarker index showed that both different contaminated soils had an effect on the earthworms and allowed to validate the ecotoxicological relevance of this battery of biomarkers for a promising integrated multi-marker approach in soil monitoring and assessment.
Keywords: monitorování životního prostředí; Biomarker index; ekotoxikologie; látky znečišťující půdu; Malondialdehyde; malondialdehyd; Comet Assay; Heavy metal; glutathiontransferasa; Environmental Monitoring; Bioaccumulation; peroxid vodíku; Glutathione Transferase; Soil Pollutants; Cadmium; Oligochaeta; katalasa; zvířata; metalothionein; biologické markery; kadmium; kometový test; Bioindicator; Metallothionein; Catalase; Biomarkers; Earthworm; Hydrogen Peroxide; Ecotoxicology; Animals